The T'boli [videorecording] a people who live without - Medina, Susan Calo.; GMA 7 (Television station : Quezon City).; Philippines. National Commission for Culture and the Arts.; Travel Time (Television program). (Manila Travel Time, 1996)
Explores the indigenous group, T'boli in South Cotabato highland who live daily with art and for whom art is not just an end product or an object but a reflection of their will, beliefs, aspirations and culture. The integration of art and life is the T'bolis bridge to ancestors world view and aspirations.
Documentary.
VHS.
Keywords: T'bolis.; Art -- Philippine -- Cotabato; Art, Tagabili; Musical instruments, T'boli.; T'bolis -- Marriage customs and rites; T'bolis -- Social life and customs